THE FUTURE OF ORTHOPAEDIC SURGERY: INTEGRATING 3D PRINTING, AI, AND BIOPRINTING - Piotr Pitrus; Karol Bednarz; Anita Krowiak; Gabriela Majka; Magdalena Kowalczyk; Karolina Krowiak; Anita Warzocha; Wiktoria Hander; Aleksandra Karnas; Maria Jasiewicz (International Journal of Innovative Technologies in Social Science, 2025)
The integration of three-dimensional (3D) printing into orthopedic surgery has significantly influenced surgical planning, implant customization, and patient. outcomes. This review explores clinical applications and the future of 3D printing, bioprinting, artificial intelligence (AI), and future 4D printing technologies in orthopedics. The use of 3D-printed anatomical models and patient-specific surgical guides has been shown to reduce operative time, intraoperative blood loss, and radiation .exposure, while improving implant fit and. surgical precision. Custom-made implants offer individual solutions for reconstructions, especially in cases of severe bone loss and musculoskeletal oncology. Emerging innovations such as AI-assisted design and bioprinted scaffolds further enhance treatment strategies. Additionally, 4D printing.introduces smart implants capable of adapting to physiology, opening new possibilities orthopedic problems. Despite challenges related to cost and production time ongoing technological progress is paving the way for wider clinical adoption.